Attempting to prepare a plastic scintillator from a biobased polymer. Issue 21 (18th November 2019) - Hamel, Matthieu; Lebouteiller, Guillaume
ABSTRACT: A new plastic scintillator was prepared from a renewable polymer source. It is composed of the mighty 2, 5‐diphenyloxazole and 1, 4‐bis(2‐methylstyryl)benzene molecules (PPO and bis‐MSB), acting as primary and secondary fluorophores, respectively, together dissolved in a polylactic acid matrix—PLA. This polymer is indeed considered as the biomass‐based equivalent of petroleum‐derived plastics in terms of mechanical and optical properties. Subsequent to the bis‐MSB emission, the emission wavelength is centered around 424 nm and the fluorescence decay time is in the nanosecond range. The material was fully characterized, and its scintillation performances were compared to a commercial PVT‐based plastic scintillator: EJ‐200. Like polystyrene‐ or polyvinyltoluene‐based scintillators, the material displayed a good response linearity with the energy of the incident gamma‐ray. However, the observed scintillation yield was rather modest, with a reported 500 ph/MeV value when excited with a gamma‐ray‐emitting 60 Co source. This preliminary test could pave the way to new and renewable polymers for unexpected applications such as nuclear physics. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48724. Abstract : Radioactivity and poly(lactic acid) shine a biobased plastic scintillator